1995
DOI: 10.1128/mcb.15.8.4545
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of TRAS1, a Novel Family of Telomeric Repeat-Associated Retrotransposons in the Silkworm, Bombyx mori

Abstract: We characterized TRAS1, a retrotransposable element which was inserted into the telomeric repetitive sequence (CCTAA) n of the silkworm, Bombyx mori. The complete sequence of TRAS1, a stretch of 7.8 kb with a poly(A) tract at the 3 end, was determined. No long terminal repeat (LTR) was found at the termini of the element. TRAS1 contains gag-and pol-like open reading frames (ORFs) which are similar to those of non-LTR retrotransposons. The two ORFs overlap but are one nucleotide out of frame (؉1 frameshift). Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 54 publications
4
95
0
3
Order By: Relevance
“…In further study, it will be clarified whether some components of Bombyx telomerase are blocked functionally and what mechanisms underlie the (TTAGG) n addition under such a low telomerase activity. In Bombyx telomeres, hundreds of copies of several families of nonLTR retrotransposons (LINE-like elements) are accumulated within the telomeric repeats [33,34]. These telomeric repeat associated retrotransposons, named TRAS and SART, are actively transcribed and possibly work on telomere elongation [35].…”
Section: Discussionmentioning
confidence: 99%
“…In further study, it will be clarified whether some components of Bombyx telomerase are blocked functionally and what mechanisms underlie the (TTAGG) n addition under such a low telomerase activity. In Bombyx telomeres, hundreds of copies of several families of nonLTR retrotransposons (LINE-like elements) are accumulated within the telomeric repeats [33,34]. These telomeric repeat associated retrotransposons, named TRAS and SART, are actively transcribed and possibly work on telomere elongation [35].…”
Section: Discussionmentioning
confidence: 99%
“…In two regions, which are shown by gray lines under the sequences, LINEs have shorter amino acid tracts compared with that of APE1. Secondary structural information (␣1-3, ␤1-14, 3 10 A, and 3 10 B) obtained by crystal analyses is shown above the amino acid sequences. The amino acids altered in mutagenesis studies (Fig.…”
Section: Tras1-en Efficiently Digests Both (Ttagg) N and (Ttag-gg) N mentioning
confidence: 99%
“…However, several endonuclease-encoding LINE have very restricted integration targets within the genome (9). TRAS1 and R1Bm, found in Bombyx mori, are the typical sequence-specific elements, which insert between T and A of the (TTAGG) n telomeric repeat and a specific site in 28 S rDNA of B. mori, respectively (10,11). Recent studies have shown that the endonuclease domain in the ORF2 of TRAS1 (12) and R1Bm (13) determines its own target sequence recognition and DNA cleavage activity.…”
mentioning
confidence: 99%
“…The telomeres of the silkworm consist of the insect telomeric repeats but harbor many types of non-LTR retrotransposons, designated TRAS and SART families (Fujiwara et al, 2005;Kubo et al, 2001;Okazaki et al, 1995). TRAS and SART are abundantly transcribed and actively transpose into TTAGG telomeric repeats in a highly sequence-specific manner.…”
Section: The Silkwormmentioning
confidence: 99%